Interactive Light Field Tilt-Shift Refocus with Generalized Shift-and-Sum - Smolic, Aljosa; Alain, Martin; Aenchbacher, Weston (My University, 2019)
Since their introduction more than two decades ago, light fields have gained considerable interest in graphics and vision communities due to their ability to provide the user with interactive visual content. One of the earliest and most common light field operations is digital refocus, enabling the user to choose the focus and depth-of-field for the image after capture. A common interactive method for such an operation utilizes disparity estimations, readily available from the light field, to allow the user to point-and-click on the image to chose the location of the refocus plane. In this paper, we address the interactivity of a lesser-known light field operation: refocus to a non-frontoparallel plane, simulating the result of traditional tilt-shift photography. For this purpose we introduce a generalized shift-and-sum framework. Further, we show that the inclusion of depth information allows for intuitive interactive methods for placement of the refocus plane. In addition to refocusing, light fields also enable the user to interact with the viewpoint, which can be easily included in the proposed generalized shift-and-sum framework.
Proceedings of European Light Field Imaging Workshop, Forthcoming.
PUBLISHED
Keywords: Light field; Digital refocus; Shift-and-sum; Tilt-shift; Camera array; Plenoptic camera; Creative Technologies; Multimedia & Creativity; Other